Evaluation of Total Fuel Aromatics in Natural Water by the Use of Solid Phase Microextraction Preconcentration and Ultraviolet Absorption Spectroscop - Abu-Shammala, Farida (Asian Journal of Chemistry, 2010)
An apparently simple and novel technique was developed to aid detection of the total fuel aromatics in natural water. The method depends upon preconcentration of the aromatic compound into poly (dimethyl siloxane) disk and the use of ultraviolet absorption spectroscopy. The equilibrium times for the fuels studied, unleaded gasoline, kerosene, and no. 1 diesel fuel are 120, 220 and 250 min respectively. The limit of detection for unleaded gasoline kerosene and no. 1 diesel fuel at their equilibrium time are 4.5, 14 and 8.9 ppb, respectively for ground water, and 9.6, 16 and 10 ppb, respectively for pond water. The total recoveries of the fuel aromatics from unleaded gasoline, kerosene, and no. 1 diesel fuel from natural water matrices are in the range of 92-96% with RSDs in the range of 2.0-12%.